Digital Business Ecosystem: Strategy, Technology, E-Commerce and Consumer Analysis - Nur Mastuti, Dian; Ayu Sofiati, Nunung; Suhendra, Agus; Prayoga, Rahmat; Puspo Arianty, Kiki (Siber International Journal of Digital Business (SIJDB), 2024)
The purpose of this article is to explore the relationship between technology, e-commerce, business strategy, and consumer analysis in the context of developing a dynamic digital business ecosystem. Based on this, businesses can see how important it is to combine these four components to increase competitiveness and achieve long-term growth in the digital era. The research method used is descriptive qualitative. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is obtained from online academic media such as Taylor & Francis, Scopus Emerald, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar, and digital reference books. The results of this article are: 1) Strategy has a significant effect on the digital business ecosystem; 2) Technology has a significant effect on the digital business ecosystem; 3) E-commerce has a significant effect on the digital business ecosystem; 4) consumer analysis has a significant effect on the digital business ecosystem.